Linguistic Approaches for Annotation, Visualization and Comparison of Prokaryotic Genomes and Environmental Sequences - Bezuidt, Oliver; Ganesan, Hamilton; Labuschange, Phillip; Emmett, Warren; Pierneef, Rian; Reva, Oleg N. (IntechOpen, 2011)
None